Respostas de estresse induzidas pela privação de sono paradoxal em ratos: neurobiologia e comparação com estressores clássicos - Moraes, Danilo Alves de [UNIFESP] (2020)
Background: Stressors are responsible for generating a set of neuronal, endocrine, autonomic and behavioral responses, coordinated by the central nervous system (CNS). In rodents, several findings demonstrate that paradoxical sleep deprivation (PSD) by the single platform method (SPM) triggers stress response. However, there is a recurrent criticism of these results, debating whether the observed changes are due to the suppression of this sleep phase or to other stressful stimuli linked to the method. Other methods of PSD produce stress responses similar to those described for the SPM, despite the differences in magnitude, which led us to propose that, regardless of the method, prolonged, unremitting PSD is a stressful stimulus responsible for such changes. The sympathetic nervous system (SNS) and the hypothalamic-pituitary-adrenal (HPA) axis are the main physiologic stress response systems. However, it is possible to assess the stress response under different perspectives, such as those involving neurochemical changes and differential activation of specific pathways, depending on the perception of the stimulus by the brain and discrimination between physical or psychological stimuli. Objectives: To indirectly compare the SPM for sleep deprivation with other classic stressors, known to be of distinct natures and evaluate the changes caused by these manipulations in a more detailed way, e.g., not only restricted to peripheral glucocorticoid release, but also to discriminate the activation of neuronal structures associated with the stress response as well as the expression of its main mediators [arginine-vasopressin (AVP), corticotropin releasing hormone (CRH) and central monoamines]. Methods: In Experiment 1, male rats were exposed to cold during 1 h (physical stressor), to predator odor during 30 min (psychological stressor) or to restraint during 1 h (mixed stressor) 1 or 4 times, once per day. In Experiment 2, the animals were submitted to PSD by the SPM, wherein the stimulus length was 1 or 4 days, uninterrupted. After the stress protocol, we evaluated: 1) AVP and CRH expression in the paraventricular nucleus of the hypothalamus (PVN) and median eminence (ME); adrenocorticotrophic hormone (ACTH) and corticosterone (CORT) plasma levels; 2) noradrenaline, dopamine and serotonin levels in the prefrontal cortex (FC), hypothalamus (HPT), amygdala (AMY), dorsal and ventral hippocampus (dHPC and vHPC); 3) EGR1 expression in the cingulate cortex (pre-limbic area, infra-limbic area, rostral region and caudal region), AMY (basolateral and central nuclei) and PVN. Results: All stimuli increased plasma ACTH and CORT levels, albeit at different magnitudes. Repeated exposure resulted in lower CORT response compared to single exposure, indicating habituation of this response, except for prolonged PSD. No differences in CRH expression were found in the PVN and ME after exposure to any of the stressors, except for PSD which was the only stimulus that reduced AVP expression in the PVN and increased it in the ME. The main changes in central monoaminergic response occurred after repeated exposure to the predator odor, including increased noradrenaline in the HPT, reduced noradrenaline and serotonin levels in the vHPC and increased serotonin turnover in the AMY. PSD also produced neurochemical changes, some of which were similar to predator odor exposure, such as reduced noradrenaline in the FC, dHPC and vHPC, increased dopamine in AMY and increased serotonin turnover in the FC, HPT and dHPC. No changes were found in EGR1 expression in the cingulate cortex and amygdala of cold, restraint and predator odor groups, after single or repeated exposure, whereas PSD reduced EGR1 expression in the cingulate cortex (infra-limbic area). Moreover, exposure to cold, restraint and PSD increased EGR1 expression in the PVN. PSD-exposed animals showed changes in the stress response at all levels assessed (HPA axis hormones, neurochemistry, neuronal activation). Conclusions: Despite the fact that PSD methodology involves association of typically physical stressors (contact with water and restricted movement), the EGR1 expression in the PVN, HPA axis and monoamine responses to PSD presented a profile that was closer to a psychological stressor. We can conclude that PSD is in fact a stressful stimulus and its nature is similar to a psychological stressor.